2018
DOI: 10.9755/ejfa.2018.v30.i11.1845
|View full text |Cite
|
Sign up to set email alerts
|

Agricultural soils strengthening employing humic acids and its effect on plant growth chilli pepper and eggplant

Abstract: The Humic substance has been recognized widely as a plant growth promoter because they induce changes in root, architecture and dynamics of growth which result in larger root size. The aim of this study was evaluating the effect Humic acids on the chili pepper (Capsicum annuum) and eggplant (Solanum melongena) plants growing in soils fertilized with urea. 200 g of soil were incorporated to the fertilizer once and the Humic acid in concentrations of 0.05%, 0.1% and 0.2%. All measurements growths were carried ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Statistically significant differences in height were recorded at the second year, with the highest plants being sprayed with 6 ml/L of humic acid at 35 and 50 days after planting. Fredy et al (2018) reported that, acid humic affected to roots of chili. Double root lengths were observed in the treatments of 0.1%, and 0.2% humic acid applied to the soil before planting.…”
Section: A the Effect Of Humic Acid And Salicylic Acid On The Growth ...mentioning
confidence: 99%
“…Statistically significant differences in height were recorded at the second year, with the highest plants being sprayed with 6 ml/L of humic acid at 35 and 50 days after planting. Fredy et al (2018) reported that, acid humic affected to roots of chili. Double root lengths were observed in the treatments of 0.1%, and 0.2% humic acid applied to the soil before planting.…”
Section: A the Effect Of Humic Acid And Salicylic Acid On The Growth ...mentioning
confidence: 99%